2010
DOI: 10.1159/000321872
|View full text |Cite
|
Sign up to set email alerts
|

EEG Patterns and Epileptic Seizures in Acute Phase Stroke

Abstract: Background: The rate of early post-stroke epileptic seizures ranges from 2 to 33%. This wide range is likely due to differences in study design, patient selection and type of neurophysiological monitoring. Electroencephalography (EEG), which is not used in the routine work-up of acute stroke, is the best neurodiagnostic technique for detecting epileptic activity, especially in patients with non-convulsive post-stroke epileptic activity. The aim of this study was to analyze patterns on EEGs performed within 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 64 publications
6
64
1
2
Order By: Relevance
“…Compared with similar studies, the frequency of EA and clinical seizures was higher [12]. The higher admission NIHSS (median 11) coupled with the inclusion of other PP as EA and the performance of EEG in later time points (up to 72 h) might explain our results.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Compared with similar studies, the frequency of EA and clinical seizures was higher [12]. The higher admission NIHSS (median 11) coupled with the inclusion of other PP as EA and the performance of EEG in later time points (up to 72 h) might explain our results.…”
Section: Discussioncontrasting
confidence: 65%
“…Several studies have shown a strong association of PP (including lateralized periodic discharges and rhythmic delta activity) with the occurrence of seizures [3,9,10,12]. It is possible that some of these patterns, especially lateralized periodic discharges, represent an interictal-ictal continuum and might warrant early treatment [5,13].…”
Section: Discussionmentioning
confidence: 99%
“…In the first 24 h after ischemic stroke, seizure occurs in ≤6.5% of patients [42], although two thirds of patients with seizures may develop status epilepticus, and rates may be >10% among patients with severe strokes [43]. Status may occur in >70% of patients with periodic discharges on EEG [42].…”
Section: Patient Selectionmentioning
confidence: 99%
“…In the first 24 h after ischemic stroke, seizure occurs in ≤6.5% of patients [42], although two thirds of patients with seizures may develop status epilepticus, and rates may be >10% among patients with severe strokes [43]. Status may occur in >70% of patients with periodic discharges on EEG [42]. In addition to seizure detection, EEG has additional benefits in characterizing poor prognosis when there is background suppression, attenuation of fast frequencies [44], or when amplitude integrated values are low on quantitative EEG [45].…”
Section: Patient Selectionmentioning
confidence: 99%
“…PLEDs may be an expression of dynamic brain damage in the very acute stage. While PLEDs are commonly associated with large cortical destructive processes, they may be seen in patients with subcortical, chronic lesions, or metabolic disturbances [32,39]. Mecarelli et al analyzed the EEGs performed within 24 h of a cohort of 232 patients admitted with acute ischemic or intraparenchymal hemorrhagic stroke.…”
Section: Electroclinical Manifestations Of Acute Strokementioning
confidence: 99%